2022
DOI: 10.1002/anie.202203982
|View full text |Cite
|
Sign up to set email alerts
|

Highly Robust CuI‐TADF Emitters for Vacuum‐Deposited OLEDs with Luminance up to 222 200 cd m−2 and Device Lifetimes (LT90) up to 1300 hours at an Initial Luminance of 1000 cd m−2

Abstract: A critical step in advancing the practical application of copper-based organic light-emitting diodes (OLEDs) is to bridge the large gap between device efficiency and operational stability at practical luminance. Described is a panel of air-and thermally stable two-coordinate Cu I emitters featuring bulky pyrazine-(PzIPr) or pyridine-fused N-heterocyclic carbene (PyIPr*) and carbazole (Cz) ligands with enhanced amide-Cu-carbene bonding interactions. These Cu I emitters display thermally activated delayed fluore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…Two-coordinate coinage metal complexes with a carbene-metal-amide (cMa) structure have recently been studied for applications in organic LEDs but have not been investigated for photoredox catalysis . These two-coordinated compounds have several attributes that are advantageous to their application as photosensitizers.…”
Section: Introductionmentioning
confidence: 99%
“…Two-coordinate coinage metal complexes with a carbene-metal-amide (cMa) structure have recently been studied for applications in organic LEDs but have not been investigated for photoredox catalysis . These two-coordinated compounds have several attributes that are advantageous to their application as photosensitizers.…”
Section: Introductionmentioning
confidence: 99%
“…Two complexes bearing respectively NN - or NO -chelating ligand demonstrated near-IR emission centered around 740−760 nm, a valuable property allowed by going from linear to trigonal coordination geometry and by the large reorganization happening at the excited state for these complexes . Five two-coordinate carbene-copper-amide complexes based on a carbene related to C 10 and carbazole ligands were synthesized and applied to OLED devices . The complexes were studied by both experimental techniques and DFT and TD-DFT calculations and displayed good emission quantum yields, as well as a radiative rate constant due to the TADF emission mechanism.…”
mentioning
confidence: 99%
“…It has been shown that coplanar ligand orientation is important for achieving appreciable oscillator strength of the S0 → S1 transition. 22,23,33 Systems with orthogonal ligands have notably low oscillator strength because the ᴨ systems of the ligand become spatially orthogonal. Au BCz MAC crystallized with a disorder of the C=O and the two methyl groups as shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…LEDs, but have never been directly investigated for solar photoredox. [17][18][19][20][21][22][23][24][25][26][27] It is valid to question whether or not two-coordinate complexes would work at all. These molecules are coordinatively unsaturated, which could allow for deleterious non-radiative decay of the excited state via solvent coordination.…”
Section: Two-coordinate Cu(i) Complexes Have Recently Been Investigat...mentioning
confidence: 99%